The Influence of Chronic Diseases on Household Chores and Leisure-time Activities - with Reference to Low Back Pain, Psoriasis, and Rheumatoid Arthritis - Leino, Mauri (Annales Universitatis Turkuensis D1290, 2017)
Chronic diseases can negatively affect a patient’s ability to perform household chores and leisure-time activities, which are an important part of everyday life. The aim of this thesis was to estimate from the patients’ perspective how chronic diseases affect a patient’s performance in household chores and leisure-time activities. The chronic diseases covered in this study are low back pain (LBP), psoriasis, and rheumatoid arthritis (RA). All the patient samples were based on a systematic sampling of patients visiting the disease specific departmental clinics at Turku University Hospital. The participants either completed a questionnaire form or answered a telephone interview. The questions were comprised of both structured answering alternatives and qualitative parts where the participants were able to present their views, in their own words. More than half of the patients with psoriasis reported difficulties in performing household chores because of the disease, with physically demanding tasks and those involving contact with water mentioned most often. Among the patients with RA, a disadvantage in household chores was perceived by over four-fifths; with the difficulties affecting a wide range of everyday household activities, and tasks related to house cleaning being mentioned most often. It had been necessary to organize assistance with household chores, because of their disease for three-quarters of the patients with LBP, a quarter of those with psoriasis, and for more than half of the RA patients. Four-fifths of the patients with LBP reported that they had had to reduce or completely give up at least one leisure-time activity because of the LBP, and this disadvantage was most pronounced among sporting activities. More than half of the patients with psoriasis had either reduced or completely given up at least one leisure-time activity because of the disease; those most often mentioned were swimming, ballgames, walking, and social activities. Among RA patients, a reduction or a giving up of leisure-time activities was reported by over three-quarters, with activities related to sport being the most affected. Patients with chronic diseases perceive themselves as having considerable disadvantages in the activities of their everyday life, especially with the ordinary things such as performing household chores and leisure-time activities; both of which cover a significant proportion of people’s time outside work. Thus, it is important to include such effects when measuring patients’ quality of life. The findings of this study describe the magnitude of this burden of chronic diseases. The study also demonstrates the type of individual and social effects that improvements in treatment outcomes can be expected to produce.

Kroonisten sairauksien aiheuttama haitta potilaan kotitoimiin ja vapaa-aikaan -käsitellen alaselkäkipua, psoriasista ja nivelreumaa. Krooniset sairaudet voivat haitata potilaan kykyä suoriutua kotitoimista ja vapaa-ajan aktiviteeteista. Väitöskirjatyön tarkoituksena on tutkia potilaan näkökulmasta, kuinka krooniset sairaudet vaikuttavat kotitoimista ja vapaa-ajan aktiviteeteista suoriutumiseen. Tutkimuksen kroonisiksi sairauksiksi valikoituivat krooninen alaselkäkipu, psoriasis ja nivelreuma. Kaikki potilasaineistot perustuvat systemaattiseen otantaan Turun yliopistollisen keskussairaalan kunkin sairauden hoidosta vastaavan klinikan potilaista. Tutkimusaineistot kerättiin joko kyselylomakkeella tai puhelinhaastatteluna. Kysymykset sisälsivät strukturoituja vastausvaihtoehtoja ja laadullisia osia, joissa potilaat saivat ominsanoin kertoa vastauksensa. Yli puolet psoriasis potilaista koki sairauden aiheuttavan haittaa kotitoimien tekemisessä. Useimmiten haittaa koettiin fyysisesti raskaammissa kotitoimissa ja toimissa, joissa iho joutuu kosketuksiin veden kanssa. Neljä viidestä nivelreumapotilaasta mainitsi sairauden aiheuttavan haittaa kotitoimien tekemisessä. Haittaa koettiin useissa toimissa, ja näistä kodin siivoaminen mainittiin useimmiten. Kolme neljäsosa alaselkäkipupotilaista, joka neljäs psoriasis potilaista ja yli puolet nivelreumapotilaista oli joutunut sairauden takia pyytämään apua kotitoimien tekemiseen. Alaselkäkipupotilaista neljä viidesosa oli joutunut vähentämään tai lopettamaan vähintään yhden vapaa-ajan aktiviteetin sairauden takia. Eniten mainitut aktiviteetit olivat urheiluharrastuksia. Yli puolet psoriasis potilaista oli joutunut vähentämään tai lopettamaan vähintään yhden vapaa-ajan aktiviteetin sairauden takia. Heillä eniten mainitut aktiviteetit olivat uinti, pallopelit, kävely ja erilaiset sosiaaliset harrasteet. Nivelreumapotilaista yli kolme neljäsosa oli joutunut vähentämään tai lopettamaan vähintään yhden vapaa-ajan aktiviteetin sairauden takia, ja näistä useimmiten mainittuja olivat urheiluharrastukset. Krooniset sairaudet voivat aiheuttaa merkittävää haittaa potilaan jokapäiväisen elämän tavallisissa askareissa, kuten kotitoimissa ja vapaa-ajan aktiviteeteissa. Potilaan elämänlaatua mitattaessa on tärkeää ottaa huomioon tämä merkittävä haitta, sillä potilaan käyttämästä ajasta, työn lisäksi, kotitoimet ja vapaa-ajan aktiviteetit kattavat merkittävän osan. Tämän tutkimuksen tulokset kuvaavat kroonisten sairauksien aiheuttaman haitan laajuutta potilaan jokapäiväiseen elämään. Tästä tutkimuksesta saatavaa tietoa voidaan käyttää arvioitaessa potilaan hoidoista saatavia yksilöllisiä ja sosiaalisia hyötyjä.